Canine parvovirus in vaccinated dogs: a field study. (16th April 2016) - Miranda, C.; Thompson, G.
Abstract : The authors report a field study that investigated the canine parvovirus (CPV) strains present in dogs that developed the disease after being vaccinated. Faecal samples of 78 dogs that have been vaccinated against CPV and later presented with clinical signs suspected of parvovirus infection were used. Fifty (64.1 per cent) samples tested positive by PCR for CPV. No CPV vaccine type was detected. The disease by CPV‐2b occurred in older and female dogs when compared with that by CPV‐2c. The clinical signs presented by infected dogs were similar when any of both variants were involved. In most cases of disease, the resulting infection by field variants occurred shortly after CPV vaccination. Two dogs that had been subjected to a complete vaccination schedule and presented with clinical signs after 10 days of vaccination, had the CPV‐2c variant associated. The phylogenetic studies showed a close relationship of the isolates in vaccinated dogs to European field strains. Despite the limited sample size in this study, the findings point to the significance of the continuous molecular typing of the virus as a tool to monitor the prevalent circulating CPV strains and access the efficacy of current vaccines. Adjustments on the vaccine types to be used may have to be evaluated again according to each epidemiological situation in order to achieve the dog's optimal immune protection against CPV.